RELATIONSHIP BETWEEN RESIDENTIAL PROPERTY PRICE INDEX AND MACROECONOMIC INDICATORS IN DUBAI HOUSING MARKET - Hepsen, Ali; Vatansever, Metin (VILNIUS GEDIMINAS TECH UNIV, 2012)
The main purpose of this study is to investigate whether there is a long-run relationship between macroeconomic indicators and property price index in Dubai. This paper uses the monthly data for the eight year period from January 2003 to December 2010. In order to identify long term equilibrium between property price index and macroeconomic indicators, cointegration analyses are utilized for the study. The results of the empirical analyses show that there is a long term positive equilibrium relationship not only between REIDIN.com Dubai Residential Property Price Index (DRPPI) and gold prices; but also between DRPPI and volume of total direct foreign trade. On the other hand, there is a negative long-run relationship between DRPPI and the number of completed residential units. In addition, there is a significant positive relation between DRPPI and the first lag of DRPPI and also the first lag of error term. Our paper is the first academic study that identifies this relationship in Dubai.
Keywords: Dubai; Real estate; Residential Property Price Index; Macroeconomic indicators; Cointegration; HETEROSKEDASTICITY; Business & Economics